The utilization of the Taguchi method on microring resonator design parameters to enhance the value of the quality factor - Aminudin, Ahmad; Hasanah, Lilik; Setyo Nugroho, Harbi; Wulandari, Chandra; Mulyanti, Budi; Eka Pawinanto, Roer; Rifqi Md Zain, Ahmad; Sugandi, Gandi; Hamidah, Ida; Indrasari, Widyaningrum; Yunas, Jumril (Institute of Advanced Engineering and Science, 2025)
This study uses the Taguchi method to optimize the quality factor (Q-factor) of microring resonators (MRRs) for sensor applications. The MRRs are compact optical components widely used in biosensors and environmental monitoring due to their sensitivity to refractive index changes. The Q-factor, a key performance metric for MRRs, is significantly influenced by structural parameters such as ring radius (R), gap (g), waveguide width (W), and waveguide height (h). We employed a finite difference time domain (FDTD) simulation to model light propagation within the MRR and compute the corresponding Q-factor to identify the optimal combination of these parameters. An L9 orthogonal array (OA) is used in the Taguchi method to analyze each factor's influence with three levels systematically. The optimization resulted in a Q-factor of 6208.44, significantly higher than the baseline value, indicating a substantial improvement. Compared to previous works, this research highlights the advantages of combining FDTD-based electromagnetic modeling with statistical optimization, offering a structured yet efficient approach to MRR design. The proposed method enhances Q-factor performance and provides scalability for practical applications in biomedical and environmental sensing. These findings underscore the utility of Taguchi-based design in advancing the field of photonic sensor optimization.